The Impact of Organizational Silence on Organizational Citizenship Behavior at Private Universities in Hodeidah City - Mabrookah Faisal Mohammed Moogam; Gamal Dirhim Ahmed Zaid (University of Science and Technology, Sana’a, Yemen, 2026)
This study aimed to identify the impact of organizational silence (OS) on organizational citizenship behavior (OCB) at private universities in Hodeidah city, Republic of Yemen. The study employed the descriptive-analytical approach to achieve its objectives and test its hypotheses. A questionnaire was used as the primary data collection tool, targeting the study population, which consisted of 200 individuals. Given the small population size, a census methodology was conducted, distributing the questionnaire to all members (both administrative and academic staff). The Statistical Package for the Social Sciences (SPSS) was utilized for statistical data analysis. The study findings revealed that OS has an impact on OCB in the universities under the study. Among the dimensions of OS, defensive silence was found to have the highest impact on OCB, followed by social silence, and finally acquiescent silence. The findings also indicated that the level of OCB was high, whereas the level of OS practiced in the studied universities was generally moderate. Based on these findings, the study recommends enhancing OCB in the examined universities by implementing training and incentive programs that encourage employees to adopt positive behaviors such as teamwork, initiative, and organizational commitment. Additionally, the study recommends activating effective communication channels and fostering an open work environment that motivates employees to express their opinions and suggestions without fear of negative consequences, thereby reducing the level of OS among university employees.